Prospects of legal semiotics - Wagner, Anne; Broekman, Jan; SpringerLink (Online Service). (Dordrecht, Netherlands Springer Netherlands, 2010)
This book examines the progress to date in the many facets - conceptual, epistemological and methodological - of the field of legal semiotics. It reflects the fulfillment of the promise of legal semiotics when used to explore the law, its processes and interpretation. This study in Legal Semiotics brings together the theory, structure and practice of legal semiotics in an accessible style. The book introduces the concepts of legal semiotics and offers an insight in contemporary and future directions which the semiotics of law is going to take. A theoretical and practical oriented synthesis of the historical, contemporary and most recent ideas pertaining to legal semiotics, the book will be of interest to scholars and researchers in law and social sciences, as well as those who are interested in the interdisciplinary dynamics of law and semiotics.   ?The dependence of law upon the media of its transmission has long constituted a controversial open border with other disciplines. Prospects of Legal Semiotics takes a radical and expansive view of possible frameworks for addressing the signs of law in an increasingly virtual and predominantly visual epoch of global dissemination. Wagner and Broekman are especially to be commended for the imaginative and rigorous manner in which they have opened legal semiotics to a novel methodological interrogation at the same time as they have encouraged analyses that go beyond the established jurisdiction of law?. Peter Goodrich Professor of Law, Cardozo School of Law  New York - USA
Part I - Deconstructing legal semiotics--Chapter 1 - Legal Semiotics and Semiotic Aspects of Jurisprudence; Bernard Jackson--Chapter 2 - Firstness and phenomenology - Peirce and Husserl on Attitude Change; Jan M. Broekman--Chapter 3 - The gift and the meaning-giving subject: a reading of Given Time; Jacques de Ville--Chapter 4 - Resources for a Dialectical Legal Semiotics? Michael Salter--Part II ?Legal Semiotics as Communication--Chapter 5 - The problems of the subjects; Louis Wolcher--Chapter 6 - Law and governance in prophetic painting: Jackson Pollock, Mark Rothko, and Gilles Deleuze'; Ronnie Lippens--Chapter 7 - Visual Law: The Changing Signifiers of Law in Popular Visual Culture; Jason Brainbridge--Chapter 8 - Legal Controversies about the Establishment of New Places of Worship in Multicultural Cities: A Semiogeographic Analysis;Massimo Leone--Selected Bibliography--Index.
Electronic reproduction.
Keywords: Semiotics (Law)